МЕТОДИ НАВЧАННЯ АНГЛІЙСЬКОЇ МОВИ ЗА ПРОФЕСІЙНИМ СПРЯМУВАННЯМ В ЕРУ ЦИФРОВИХ ТЕХНОЛОГІЙ - М. М. Прокопчук; Л. Ф. Віннікова (International Journal of Innovative Technologies in Social Science, 2020)
The article deals with the issue of adjusting modern teaching methods of teaching English for specific purposes to digital era challenges.According to the authors’, modern teaching methods of communicative approach ought to adopted to be used in the virtual classes. Moreover, there is a number of benefits, which should be taken into consideration whist conduction online classes.It is highlighted that the students of Z generation have developed certain psychological peculiarities. As a result, they affect the methods and techniques that the teacher has to apply for successful professional foreign language development. This competence is developed along with subject information competence.